Epidemiology and survival of HPV-related tonsillar carcinoma - Psychogios, Georgios; Alexiou, Christoph; Agaimy, Abbas; Brunner, Kathrin; Koch, Michael; Mantsopoulos, Konstantinos; Tomppert, Andrea; Iro, Heinrich (Cancer Medicine, 2014)
The aim of this study was to determine the proportion of human papilloma virus (HPV)-positive cases in tonsillar carcinomas and investigate its development over the last decade. Further aim was to show the oncologic results in accord to HPV status and various treatment modalities. A retrospective study was conducted between 2000 and 2012 and included 275 patients treated for tonsillar carcinoma. P16 immunohistochemistry was used as a surrogate marker for HPV-associated carcinogenesis. A total of 101 (36.7%) patients proved to be p16 positive and 174 p16 negative. 80.2% of the p16-positive cases presented with T1-2 tumor. Of the early-stage patients, 79% of the p16-positive and 52.3% of the p16-negative presented with lymph node metastases. The percentage of p16-positive patients increased from 23.2% in the period 2005-2007 to 58.6% in the period 2010-2012 in the whole population and from 30.9% to 76.9% in T1-2 carcinomas. Early T-category p16-positive carcinomas had significantly better disease-specific survival (92.4% vs. 75.5%, P = 0.007) and overall survival (OS, 79.6% vs. 54.3%, P < 0.001) compared to p16-negative tumors. This study showed an increase in the percentage of p16-positive patients in tonsillar carcinoma from 23.2% in the years between 2005 and 2007 to 58.6% between 2010 and 2012. The majority (80.2%) of p16-positive patients presented with early T-category tumor but most of these (79.0%) had also lymph node metastases. Nevertheless, p16-positive patients had excellent oncologic results after surgery and adjuvant radiotherapy and could be considered for de-escalation of treatment.
EVALuna2:6679